Intermediate lengths of the C9ORF72 hexanucleotide repeat expansion may synergistically contribute to attention deficit hyperactivity disorder in child and his father: case report. Issue 2 (4th March 2021) - Maj, Carlo; Chiarenza, Giuseppe Augusto; Faraone, Stephen V.; Miriam, Ciani; Gennarelli, Massimo; Bonvicini, Cristian; Scassellati, Catia
ABSTRACT: We have summarized the abstract section as follows: "We report a son and his father aﬀected by Attention Deﬁcit Hyperactivity Disorder (ADHD). They belonged to a larger cohort (116 ADHD children, 20 related parents, 77 controls) wholly genotyped for C9ORF72  expansion. Ten ADHD susceptibility genes were further investigated in the family. We revealed that son and father shared an intermediate C9ORF72  expansion and common variants in CDH23,   ITGAE  and  MTRR . Bioinformatics highlighted a C9ORF72 - MTRR  interaction. This case-report underlines that in relatives with ADHD, carrying variants in ADHD susceptibility genes, the intermediate C9ORF72  repeats might have a potentially pathogenetic synergistic eﬀect, supporting the multifactorial polygenic aetiopathogenetic proﬁle of disease".